(untitled) - Capachietti, Leslie (New York, 2010)
Explains how to use QuickBooks to set-up and manage bookkeeping systems, track invoices, pay bills, manage payroll, generate reports, and determine job costs.
Keywords: Small business,Doanh nghiệp nhỏ; Accounting,Computer programs,Kế toán,Chương trình máy tính